Discriminations positives, enseignement supérieur et peuples indigènes au Brésil : un survol - Antonio Carlos De Souza Lima (Cahiers de la Recherche sur l'Education et les Savoirs)
The objective of this text is to present some significant and important aspects of what we mean when we talk about affirmative action for Brazil’s Native peoples. We begin with a brief overview of the history of Indian affairs under Brazil’s republican state. We then discuss how Native peoples came to demand access to higher education in Brazil. Finally, we look at what kinds of affirmative action programs can meet Native peoples’ needs in the challenge of bringing them into Brazilian universities.